Integrating Science and Politics for Public Health - Fafard, Patrick; Cassola, Adèle; de Leeuw, Evelyne (Palgrave Studies in Public Health Policy Research, 2022)
This open access book bridges the divide between political science and public health, whilst simultaneously embracing the complexities and differences of both. Although public health is inherently political, the tools and insights of political science are often ignored in public health scholarship. Bringing together academics and researchers working at the intersection of both, the book demonstrates how integrating these fields can help reconcile the roles of politics and scientific evidence in policymaking. It also highlights the key conceptual, methodological and substantive implications for bridging this divide, and charts a path forward for a movement towards political science with public health. It will be of interest to academics, researchers and students interested in public health, political science, public policy, and the role of scientific evidence in policymaking.